2023
DOI: 10.3389/fpubh.2023.1106728
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical homeostasis in ocular diseases: A mini-review

Abstract: Diabetes mellitus-induced hyperglycemia is responsible for multiple pathological ocular alternations from vasculopathy to biomechanical dyshomeostasis. Biomechanical homeostasis is crucial to maintain the normal physiological condition of the eyes. Biomechanical features vary in eye tissues regarding different anatomical positions, tissue components, and cellular functions. The disturbance in biomechanical homeostasis may result in different ocular diseases. In this review, we provide a preliminary sketch of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…These results showed that Piezo1 is an essential regulator in cell cycle progression in ONH astrocytes [54]. Other studies verified that chemical inhibition or genetic ablation of these mechanosensitive channels significantly ameliorates pathological phenotypes of optic nerve degeneration caused by IOP elevation, indicating the potential therapeutic roles of targeting mechanosensitive channels in glaucoma [52, 54, 55].…”
Section: Basic Research Of “Dual‐pressure Theory”mentioning
confidence: 88%
See 3 more Smart Citations
“…These results showed that Piezo1 is an essential regulator in cell cycle progression in ONH astrocytes [54]. Other studies verified that chemical inhibition or genetic ablation of these mechanosensitive channels significantly ameliorates pathological phenotypes of optic nerve degeneration caused by IOP elevation, indicating the potential therapeutic roles of targeting mechanosensitive channels in glaucoma [52, 54, 55].…”
Section: Basic Research Of “Dual‐pressure Theory”mentioning
confidence: 88%
“…To update, this measuring method has been applied for early monitoring of spaceflight-associated neuroocular syndrome (SANS). SANS is featured as fluid redistribution in the optic nerve sheath and the cerebrospinal fluid cavity due to longterm exposure to the unique microgravity environment during extended spaceflight [55,63]. This novel and noninvasive method could help rapidly obtain a relatively accurate ICP through a mathematical formula based on ultrasonography; its future application in the detection and assessment of NTG is promising.…”
Section: Measurement Techniques Of Tlcpdmentioning
confidence: 99%
See 2 more Smart Citations
“…Mohammadi M et al explored the mechanisms involved from a cell biological perspective: Cell proliferation in the lumen of the vein at the level of the lamina cribrosa and displacement of the vessel in the anterior portion of the optic nerve have been suggested to be causes of central/hemicentral RVOs 30 . In recent years, as the study of biomechanics in ocular diseases has been gradually deepened, the biomechanical mechanisms associated with RVO have been gradually revealed 31 . The physical obstruction of the retinal venous system is generally induced by thrombosis, deformation of the vein wall, and external biomechanical compression secondary to glaucoma 32 .…”
Section: Discussionmentioning
confidence: 99%